1991
DOI: 10.1073/pnas.88.24.11153
|View full text |Cite
|
Sign up to set email alerts
|

Rapid de novo generation of defective interfering RNA by cucumber necrosis virus mutants that do not express the 20-kDa nonstructural protein.

Abstract: It is generally believed that serial passage at high multiplicity of infection (moi) is required for the generation of defective interfering (DI) particles. High levels of DI RNAs are found associated with persistent infections initiated with laboratory cultures of cucumber necrosis virus (CNV). Two synthetic CNV transcripts that were derived through site-directed mutagenesis of a highly infectious CNV cDNA clone and that do not express the CNV 20-kDa nonstructural protein were found to generate high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
39
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 24 publications
3
39
0
1
Order By: Relevance
“…1 b). This pattern of retained CNV genomic sequences has been observed in CNV DI RNAs recently sequenced in another laboratory (Y.-C. Chang, T. J. Morris & A. Jackson, personal communication) and those generated from the 20K mutant of CNV (Rochon, 1991) as well as DI RNAs from the related tombusviruses TBSV-Ch (Hillman et aL, 1987;Knorr et al, 1991) and CyRSV (Burgyan et al, 1989(Burgyan et al, , 1991Rubino et al, 1990). At their 5' ends, all clones maintained sequences up to and immediately upstream of the CNV 33K start codon and seven of the nine clones retained the actual start codon.…”
mentioning
confidence: 53%
See 4 more Smart Citations
“…1 b). This pattern of retained CNV genomic sequences has been observed in CNV DI RNAs recently sequenced in another laboratory (Y.-C. Chang, T. J. Morris & A. Jackson, personal communication) and those generated from the 20K mutant of CNV (Rochon, 1991) as well as DI RNAs from the related tombusviruses TBSV-Ch (Hillman et aL, 1987;Knorr et al, 1991) and CyRSV (Burgyan et al, 1989(Burgyan et al, , 1991Rubino et al, 1990). At their 5' ends, all clones maintained sequences up to and immediately upstream of the CNV 33K start codon and seven of the nine clones retained the actual start codon.…”
mentioning
confidence: 53%
“…In addition, plants infected with CNV-Lc displayed attenuated symptoms in comparison with plants inoculated with synthetic wild-type (wt) CNV transcripts (Johnston & Rochon, 1990). These observations taken in conjunction with the fact that synthetic CNV mutants that do not express the 20K protein rapidly generate DI RNAs de novo (Rochon, 1991) suggested that the 400 nucleotide RNAs associated with CNV-Lc infection may be DI RNAs and further that the wt CNV genome, like the 20K mutant genome, is capable of generating DI RNAs de novo. In this paper we demonstrate that the 400 nucleotide RNAs are in fact DI RNAs and are likely to be responsible for the symptom attenuation associated with CNV-Lc.…”
mentioning
confidence: 98%
See 3 more Smart Citations